Garfield fat cat 3-pack. Volume 3 - Davis, Jim, 1945 July 28- (New York : Ballantine Books, 2007)
Collects in one volume three previously published collections of the Garfield comic strip featuring the comic strip antics of Garfield, Odie, and Jon.
Garfield sits around the house -- Garfield tips the scales -- Garfield loses his feet.
5.4
5-8
Keywords: Garfield (Fictitious character) -- Comic books, strips, etc. -- Fiction; Cats -- Comic books, strips, etc. -- Fiction; Human-animal relationships -- Comic books, strips, etc. -- Fiction; Garfield (Fictitious character) -- Juvenile fiction; Cats -- Juvenile fiction; American wit and humor; Cartoons and comics; Humorous fiction; Comic books, strips, etc; Graphic novels; Comics (Graphic works)